Catalytic hydrodeoxygenation of jojoba oil to the green-fuel application on Ni-MoS/Mesoporous zirconia-silica catalysts. (August 2019) - Ramesh, Arumugam; Tamizhdurai, Perumal; Shanthi, Kannan
Abstract: Zirconia modified mesoporous silica such as Zr-SBA-15, Zr-KIT-6, Zr-SiO2, and Zr-FSM-16 with Si/Zr = 10 ratio over Ni-MoS catalysts were prepared under the hydrothermal condition and compared with Ni-MoS/Zr-Al (10). The prepared materials were characterized by various techniques like X-ray diffraction analysis (XRD), N2 -sorption studies, diffuse reflectance measurement–UV-Vis spectrophotometers (DR-UV-vis), NH3 -temperature-programmed desorption (NH3 -TPD)/H2 -Temperature programmed reduction (H2 -TPR), Laser-Raman, high resolution transmission electron microscopy (HRTEM) and fourier-transform infrared spectroscopy (FT-IR) techniques. The activity of materials was investigated in hydrodeoxygenation (HDO) of jojoba oil to produce long-chain hydrocarbons at 225–375 °C under 10–40 bar H2 pressure in a stainless steel fixed bed reactor. Among the catalysts tested, Ni-MoS/Zr-K (10) exhibited the highest catalytic activity of 90% conversion and 79% yield of C18–C22 hydrocarbon. The structure-activity relationships and product distributions were also discussed in detail. Graphical abstract: Image 1 Highlights: Ni-MoS over mesoporous zirconia-silicate catalysts under hydrothermal condition. Catalysts were tested for vapour phase hydrodeoxygenation of Jojoba oils. High oxygen removal efficiency was observed at 350 °C under 30 bar H2 Pressure. The absence of internal and external mass transfer resistance is ascertained.